Is Corporate Social Responsibility (CSR) Associated with Tax Avoidance? Evidence from Irresponsible CSR Activities - Hoi, Chun Keung; Wu, Qiang; Zhang, Hao (The Accounting Review, 2013)
ABSTRACT: We examine the empirical association between corporate social responsibility (CSR) and tax avoidance. Our findings suggest that firms with excessive irresponsible CSR activities have a higher likelihood of engaging in tax-sheltering activities and greater discretionary/permanent book-tax differences. Moreover, at the onset of FASB Interpretation No. 48, these firms have more uncertain tax positions; also, these firms' initial tax positions are likely supported by weaker facts and circumstances as indicated by their larger post-FIN 48 settlements with tax authorities and their higher likelihood of a net decrease in the overall level of uncertain tax positions after FIN 48. Collectively, these results suggest that firms with excessive irresponsible CSR activities are more aggressive in avoiding taxes, lending credence to the idea that corporate culture affects tax avoidance. Data Availability: Data are available from public sources identified in the study.